ANALYSIS OF THE EFFECT OF IMPLEMENTATION OF A MODERN TAX ADMINISTRATION SYSTEM ON EMPLOYEE PERFORMANCE PRATAMA TAX SERVICES OFFICE POLONIA FIELDS - Adila Zega; Prihatin Lumbanraja; Khaira Amalia Fachruddin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The increasing role of taxes as the main source of state revenue as well as public demands for clean and transparent tax management have encouraged the Directorate General of Taxes to carry out reforms in the form of improvements to tax policies and the tax administration system. In principle, the concept of modernizing tax administration is a change to the tax administration system that can change the mindset and behavior of officials as well as organizational values ​​so that it can make the DJP a professional institution with a good image in society. One of the objectives of implementing tax administration reform is to improve performance. This research aims to find out more clearly about the performance of KPP Pratama Medan Polonia with the implementation of the Modern Tax Administration System (SAPM) and the relationship between the application of SAPM and the performance of KPP Pratama Medan Polonia. In developing this research supporting theories regarding Organizational Structure, Organizational Procedures, Strategy were used. Organizations and Organizational Culture. Apart from that, to better understand the extent of the influence of Organizational Structure, Organizational Procedures, Organizational Strategy and Organizational Culture on employee performance, an in-depth understanding of employee performance theories is needed. Empirical tests were carried out on 105 employees to obtain data on Organizational Structure, Organizational Procedures, Organizational Strategy and Organizational Culture which so far have been deemed unable to provide hope for employees. The analytical tool used in this research is multiple regression. It turns out that Organizational Structure, Organizational Procedures, Organizational Strategy and Organizational Culture have a positive effect on employee performance.